Developing a model for integrating sexual and reproductive health services with HIV prevention and care in KwaZulu-Natal, South Africa - Cecilia Milford; Fiona Scorgie; Letitia Rambally Greener; Zonke Mabude; Mags Beksinska; Abigail Harrison; Jennifer Smit (BMC, 2018)
Abstract Background There are few rigorous studies evaluating the benefits of vertical versus integrated delivery of healthcare services, and limited published studies describing conceptual models of integration at service-delivery level in public healthcare facilities. This article seeks to fill this gap, by describing the development of a district-based model for integrating sexual and reproductive health (SRH) and HIV services in KwaZulu-Natal, South Africa. Methods Baseline data were collected from seven urban public healthcare facilities through client and provider interviews, and a facility inventory was completed to assess current service integration practices. Feedback sessions were held with health providers from participating facilities to share data collected and explore appropriate integration scenarios. A conceptual model of potential service integration was then designed, and subsequently implemented and evaluated in the research sites. Results Key principles of the model included a focus on health system strengthening and strong community input and involvement. The model was designed primarily to support the integration of family planning into HIV services, and included measures to improve client and commodity monitoring; capacity building through training and mentorship; and a 'health navigation' strategy to strengthen referrals within and between public healthcare facilities. Endline evaluation data were collected in the same facilities following implementation of the model. Conclusions This manuscript demonstrates the utility of the conceptual model. It shows that service integration can be accomplished in a phased manner with support of community and healthcare providers. In addition, local context must be taken into account and the components of the model should be flexible to suit the needs of the health system.